Management - Pamela S. Lewis (Thomson/South-Western, 2007)
The extended study guide for Management was updated by Tish Matuszek, Troy University. For each chapter, this comprehensive guide includes learning objectives with detailed descriptions; a chapter outline; multiple choice and agree or disagree questions with answers; exercises; and a chapter summary